2019
DOI: 10.1101/806125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Translation Complex Profiling Reveals Staged Initiation and Co-translational Assembly of Initiation Factor Complexes

Abstract: Translational control targeting mainly the initiation phase is central to the regulation of gene expression. Understanding all of its aspects requires substantial technological advancements. Here we modified yeast Translational Complex Profile sequencing (TCP-seq), related to ribosome profiling, and adopted it for mammalian cells. Human TCP-seq, capable of capturing footprints of 40S subunits (40Ses) in addition to 80S ribosomes (80Ses), revealed that mammalian and yeast 40Ses distribute similarly across 5'UTR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Our work also provides insight into how uORF features impact their ability to induce NMD. Reinitiation after uORF translation can protect human mRNA from NMD (Lindeboom et al, 2016;Zhang and Maquat, 1997), and short uORFs are known to reinitiate more efficiently than long ones (Gunišová et al, 2017(Gunišová et al, , 2016 likely due to increased retention of initiation factors (Bohlen et al, 2020;Wagner et al, 2020). Consistent with this, we found short uORFs induce less NMD than long uORFs.…”
Section: Discussionsupporting
confidence: 83%
“…Our work also provides insight into how uORF features impact their ability to induce NMD. Reinitiation after uORF translation can protect human mRNA from NMD (Lindeboom et al, 2016;Zhang and Maquat, 1997), and short uORFs are known to reinitiate more efficiently than long ones (Gunišová et al, 2017(Gunišová et al, , 2016 likely due to increased retention of initiation factors (Bohlen et al, 2020;Wagner et al, 2020). Consistent with this, we found short uORFs induce less NMD than long uORFs.…”
Section: Discussionsupporting
confidence: 83%
“…In line with a recent report that the human eIF3 complex remains attached to 80S ribosomes in early elongation (Wagner et al 2020), we observed the bulk of read clusters comprising EIF-3.G(WT) and EIF-3.G(C130Y) footprints mapping between (-)150 to (+)200 nucleotides of the start codon ( Fig. 4D).…”
Section: The Activity Of Eif-3g(c130y) Requires Its Rrmsupporting
confidence: 91%
“…We used selective ribosome footprinting (Bohlen et al, 2020, Oh, Becker et al, 2011, Wagner et al, 2020) to determine the position on endogenous mRNAs of ribosomes containing phosphorylated Ribosomal Protein S6 (RPS6) (Figure 1A). Immunoprecipitation (IP) of ribosomes with phospho-RPS6 antibody was strongly reduced when RPS6 phosphorylation was inhibited with Torin1 (Figure 1B), indicating that the IP is specific, and that in these cells RPS6 is mainly phosphorylated by S6K downstream of mTOR.…”
Section: Resultsmentioning
confidence: 99%
“…Selective ribosome footprinting is a method that identifies the location of specific ribosome sub-populations on endogenous mRNAs in human cells (Bohlen, Fenzl et al, 2020, Schibich, Gloge et al, 2016, Wagner, Herrmannova et al, 2020). This method employs immunoprecipitation to isolate ribosomes bound to specific factors such as initiation factors or chaperones, followed by sequencing of their footprints to identify their locations.…”
Section: Introductionmentioning
confidence: 99%